The Peculiarities of the Resistance in Child Psychotherapy - Khanamiryan, Irina (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
The article discusses the main characteristics of resistance in child psychotherapy. The resistance is very important element of psychotherapy, which gives a chance for unconscious defence from therapeutic intervention and for seeming comfort of life. In child psychotherapy, both the child and his/her parents can resist the therapy. Child’s resistance may have various manifestations and various reasons depending on the stage of the therapy. In the article, the reasons as well as behavioral manifestations and ways of overcoming the child and parents’ resistance are considered.